Advanced oxidation and reduction processes for PFAS treatment: Transformation products, toxicity risks, and detoxification challenge - Shilpi Verma; Stephan Zimmermann; Harald Horn (Current Opinion in Environmental Science & Health, 2026)

Geographic and Genomic Signatures of a Dynamic Evolutionary History in Lake Tanganyika's Synodontis Catfish Radiation - Gernot K. Englmaier; Stephan Koblmüller; Veronika Bartáková; Anja Palandačić; Holger Zimmermann; Martin Reichard (Journal of Biogeography, 2026)
Aim Lacustrine systems generally exhibit greater habitat stability than riverine systems, yet some lakes have experienced substantial lake‐level fluctuations throughout the Pleistocene. These environmental perturbations repeatedly altered habitat availability critical to the evolution of their diverse fish communities. In this context, we inferred phylogenetic relationships and divergence times of lacustrine Synodontis catfishes in Lake Tanganyika. We then focused on three closely related species with distinct ecomorphological specializations ( Synodontis petricola , S. polli , S. irsacae ) to further investigate their evolutionary dynamics and elucidate responses to a temporally dynamic lacustrine environment. Location Lake Tanganyika, East Africa. Taxa Synodontis spp. (Mochokidae). Methods We used mitochondrial genomes for phylogenetic reconstruction and divergence time estimation, mitochondrial COI sequences for haplotype network analysis, and genome‐wide SNPs from ddRADseq to assess population structure, demographic history, and patterns of gene flow. Results Mitochondrial genomes indicate that diversification within lacustrine Synodontis of Lake Tanganyika occurred in two main phases during the Pleistocene (2.5–1.5 Ma and 1.0–0.5 Ma), coinciding with pronounced lake‐level fluctuations and palaeoclimatic shifts. Across three closely related but ecologically distinct species, S. petricola and S. polli exhibited mitonuclear discordance—with distinct mtDNA lineages in the northern and southern lake basins—and also showed strong population structure based on nuclear genomic SNP data, whereas S. irsacae lacked geographically structured mtDNA lineages and displayed weaker nuclear differentiation. Demographic reconstructions revealed asynchronous, species‐specific expansions across lake basins, and gene‐flow modelling indicated introgression across all species following a period of isolation after divergence. Main Conclusions Our results show that—in Lake Tanganyika—complex phylogeographic patterns in lacustrine fishes can arise through combined effects of lake‐level fluctuations, ecological specialization, and spatially variable gene flow. These findings highlight how dynamic environmental histories in lacustrine systems can profoundly shape diversification of their biodiversity.

Efficient biobanking of human lung tissue slices enabled by advanced ice-free cryopreservation - Saskia Altmaier; Frank Ihmig; Klaudia Grieger; Vanessa Neuhaus; Helena Obernolte; Florian Schmieder; Stephan Behrens; Ina Meiser; Julia Neubauer; Frank Sonntag; Katherina Sewald; Heiko Zimmermann (Cryobiology, 2025)

High concentrations of Printex 90 carbon black ultrafine particles disturb the epithelial barrier in human primary respiratory mucosa models - Totta Ehret Kasemo; Maximilian Oppmann; Sofia Dembski; Maria Steinke; Elena Lajtha; Helena Moratin; Manuel Stöth; Agmal Scherzad; Mathilde Noémie Delaval; Ralf Zimmermann; Sebastiano Di Bucchianico; Stephan Hackenberg; et al. (Environmental Toxicology and Pharmacology, 2025)

Mixed Parentage Broods Indicate Group Spawning in the Brood Parasitic Cuckoo Catfish - Holger Zimmermann; Kristina M. Sefc; Radim Blažek; Veronika Bartáková; Anna Bryjová; Cyprian Katongo; Stephan Koblmüller; Martin Reichard (Molecular Ecology, 2025)
Obligate brood parasites delegate the workload of costly parental care to their hosts. Theory predicts that release from demanding parental care increases the importance of other factors to shape mating patterns. However, behavioural observations and parentage estimates are notoriously difficult to obtain in species with covert reproductive strategies, such as brood parasites, and evidence for their mating strategies are scarce. Molecular genetic methods provide a powerful tool to identify concealed mating patterns. Here, we reconstruct the parentage of cuckoo catfish ( Synodontis multipunctatus ) clutches collected in the wild using a combination of newly developed microsatellite markers, mitochondrial markers, and maximum likelihood estimates of pairwise relatedness. Cuckoo catfish parasitise mouthbrooding cichlids in Lake Tanganyika, but a natural spawning of the brood parasite has never been observed. We examined 429 females of confirmed host cichlid species (parasitism prevalence 6%; 24 parasitised clutches with 1–14 embryos) and found that 46% of clutches with three or more offspring (i.e., 6 out of 13) were parented by more than two catfish individuals. We demonstrated variable mating patterns including polyandrous and polygynous mating, and host sharing by separate, genetically monogamous, catfish pairs. This indicates that cuckoo catfish parasitism involves groups of catfish with reduced capability to monopolise mating opportunities. In general, our results demonstrate how reproductive strategy and mating patterns in a species with concealed breeding behaviour can be investigated and provide valuable insights into the mating system of a brood parasitic species other than hitherto studied avian brood parasites.

Perspectives: Resilient forests need joint forces for better inventorying and monitoring - Marco Ferretti; Arthur Gessler; Nathalie Cools; Stefan Fleck; Rossella Guerrieri; Tamara Jakovljević; Manuel Nicolas; Tiina M. Nieminen; Diana Pitar; Nenad Potočić; Stephan Raspe; Marcus Schaub; et al. (Forest Ecology and Management, 2024)

Degradation and mineralization of anti-cancer drugs Capecitabine, Bicalutamide and Irinotecan by UV-irradiation and ozone - Stephan Zimmermann; Messika Revel; Ewa Borowska; Harald Horn (Chemosphere, 2024)

Long-term biomass dynamics of temperate forests in Europe after cessation of management - Jokin Idoate-Lacasia; Jonas Stillhard; Jeanne Portier; Peter Brang; Stephan Zimmermann; Christof Bigler; Harald Bugmann; Martina L. Hobi (Forest Ecology and Management, 2024)

Climate regulation processes are linked to the functional composition of plant communities in European forests, shrublands, and grasslands - Stephan Kambach; Fabio Attorre; Irena Axmanová; Ariel Bergamini; Idoia Biurrun; Gianmaria Bonari; Maria Laura Carranza; Alessandro Chiarucci; Milan Chytrý; Jürgen Dengler; Emmanuel Garbolino; Valentin Golub; et al. (Global Change Biology, 2024)
Terrestrial ecosystems affect climate by reflecting solar irradiation, evaporative cooling, and carbon sequestration. Yet very little is known about how plant traits affect climate regulation processes (CRPs) in different habitat types. Here, we used linear and random forest models to relate the community‐weighted mean and variance values of 19 plant traits (summarized into eight trait axes) to the climate‐adjusted proportion of reflected solar irradiation, evapotranspiration, and net primary productivity across 36,630 grid cells at the European extent, classified into 10 types of forest, shrubland, and grassland habitats. We found that these trait axes were more tightly linked to log evapotranspiration (with an average of 6.2% explained variation) and the proportion of reflected solar irradiation (6.1%) than to net primary productivity (4.9%). The highest variation in CRPs was explained in forest and temperate shrubland habitats. Yet, the strength and direction of these relationships were strongly habitat‐dependent. We conclude that any spatial upscaling of the effects of plant communities on CRPs must consider the relative contribution of different habitat types.

Lack of host specialization despite selective host use in brood parasitic cuckoo catfish - Martin Reichard; Stephan Koblmüller; Radim Blažek; Holger Zimmermann; Cyprian Katongo; Anna Bryjová; Josef Bryja (Molecular Ecology, 2023)
Host–parasite dynamics involve coevolutionary arms races, which may lead to host specialization and ensuing diversification. Our general understanding of the evolution of host specialization in brood parasites is compromised by a restricted focus on bird and insect lineages. The cuckoo catfish ( Synodontis multipunctatus ) is an obligate parasite of parental care of mouthbrooding cichlids in Lake Tanganyika. Given the ecological and taxonomic diversity of mouthbrooding cichlids in the lake, we hypothesized the existence of sympatric host‐specific lineages in the cuckoo catfish. In a sample of 779 broods from 20 cichlid species, we found four species parasitized by cuckoo catfish (with prevalence of parasitism of 2%–18%). All parasitized cichlids were from the tribe Tropheini, maternal mouthbrooders that spawn over a substrate (rather than in open water). Phylogenetic analysis based on genomic (ddRAD sequencing) and mitochondrial (Dloop) data from cuckoo catfish embryos showed an absence of host‐specific lineages. This was corroborated by analyses of genetic structure and co‐ancestry matrix. Within host species, parasitism was not associated with any individual characteristic we recorded (parent size, water depth), but was costly as parasitized parents carried smaller clutches of their own offspring. We conclude that the cuckoo catfish is an intermediate generalist and discuss costs, benefits and constraints of host specialization in this species and brood parasites in general.

Long-term N-addition alters the community structure of functionally important N-cycling soil microorganisms across global grasslands - Beat Frey; Barbara Moser; Bjorn Tytgat; Stephan Zimmermann; Juan Alberti; Lori A. Biederman; Elizabeth T. Borer; Arthur A.D. Broadbent; Maria C. Caldeira; Kendi F. Davies; Nico Eisenhauer; Anu Eskelinen; et al. (Soil Biology and Biochemistry, 2023)

Elevation dependent response of soil organic carbon stocks to forest windthrow - Mathias Mayer; Silvan Rusch; Markus Didion; Andri Baltensweiler; Lorenz Walthert; Fabienne Ranft; Andreas Rigling; Stephan Zimmermann; Frank Hagedorn (Science of The Total Environment, 2023)

Soil–plant interactions modulated water availability of Swiss forests during the 2015 and 2018 droughts - Katrin Meusburger; Volodymyr Trotsiuk; Paul Schmidt‐Walter; Andri Baltensweiler; Philipp Brun; Fabian Bernhard; Mana Gharun; Raphael Habel; Frank Hagedorn; Roger Köchli; Achilleas Psomas; Heike Puhlmann; et al. (Global Change Biology, 2022)
Central Europe has been experiencing unprecedented droughts during the last decades, stressing the decrease in tree water availability. However, the assessment of physiological drought stress is challenging, and feedback between soil and vegetation is often omitted because of scarce belowground data. Here we aimed to model Swiss forests' water availability during the 2015 and 2018 droughts by implementing the mechanistic soil‐vegetation‐atmosphere‐transport (SVAT) model LWF‐Brook90 taking advantage of regionalized depth‐resolved soil information. We calibrated the model against soil matric potential data measured from 2014 to 2018 at 44 sites along a Swiss climatic and edaphic drought gradient. Swiss forest soils' storage capacity of plant‐available water ranged from 53 mm to 341 mm, with a median of 137 ± 42 mm down to the mean potential rooting depth of 1.2 m. Topsoil was the primary water source. However, trees switched to deeper soil water sources during drought. This effect was less pronounced for coniferous trees with a shallower rooting system than for deciduous trees, which resulted in a higher reduction of actual transpiration (transpiration deficit) in coniferous trees. Across Switzerland, forest trees reduced the transpiration by 23% (compared to potential transpiration) in 2015 and 2018, maintaining annual actual transpiration comparable to other years. Together with lower evaporative fluxes, the Swiss forests did not amplify the blue water deficit. The 2018 drought, characterized by a higher and more persistent transpiration deficit than in 2015, triggered widespread early wilting across Swiss forests that was better predicted by the SVAT‐derived mean soil matric potential in the rooting zone than by climatic predictors. Such feedback‐driven quantification of ecosystem water fluxes in the soil–plant‐atmosphere continuum will be crucial to predicting physiological drought stress under future climate extremes.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

The phosphorylated pathway of serine biosynthesis is crucial for indolic glucosinolate biosynthesis and plant growth promotion conferred by the root endophyte Colletotrichum tofieldiae - Sandra E. Zimmermann; Samira Blau; Henning Frerigmann; Stephan Krueger (Plant Molecular Biology, 2021)
Key message Phosphoglycerate Dehydrogenase 1 of the phosphorylated pathway of serine biosynthesis, active in heterotrophic plastids, is required for the synthesis of serine to enable plant growth at high rates of indolic glucosinolate biosynthesis. Abstract Plants have evolved effective strategies to defend against various types of pathogens. The synthesis of a multitude of specialized metabolites represents one effective approach to keep plant attackers in check. The synthesis of those defense compounds is cost intensive and requires extensive interaction with primary metabolism. However, how primary metabolism is adjusted to fulfill the requirements of specialized metabolism is still not completely resolved. Here, we studied the role of the phosphorylated pathway of serine biosynthesis (PPSB) for the synthesis of glucosinolates, the main class of defensive compounds in the model plant Arabidopsis thaliana . We show that major genes of the PPSB are co-expressed with genes required for the synthesis of tryptophan, the unique precursor for the formation of indolic glucosinolates (IG). Transcriptional and metabolic characterization of loss-of-function and dominant mutants of ALTERED TRYPTOPHAN1- like transcription factors revealed demand driven activation of PPSB genes by major regulators of IG biosynthesis. Trans-activation of PPSB promoters by ATR1/MYB34 transcription factor in cultured root cells confirmed this finding. The content of IGs were significantly reduced in plants compromised in the PPSB and these plants showed higher sensitivity against treatment with 5-methyl-tryptophan, a characteristic behavior of mutants impaired in IG biosynthesis. We further found that serine produced by the PPSB is required to enable plant growth under conditions of high demand for IG. In addition, PPSB-deficient plants lack the growth promoting effect resulting from interaction with the beneficial root-colonizing fungus Colletotrichum tofieldiae .

Reconstruction of Historic Forest Cover Changes Indicates Minor Effects on Carbon Stocks in Swiss Forest Soils - Sia Gosheva; Lorenz Walthert; Pascal A. Niklaus; Stephan Zimmermann; Urs Gimmi; Frank Hagedorn (Ecosystems, 2017)

Aboveground vertebrate and invertebrate herbivore impact on net N mineralization in subalpine grasslands - Anita C. Risch; Martin Schütz; Martijn L. Vandegehuchte; Wim H. van der Putten; Henk Duyts; Ursina Raschein; Dariusz J. Gwiazdowicz; Matt D. Busse; Deborah S. Page-Dumroese; Stephan Zimmermann (Ecology, 2015)
Aboveground herbivores have strong effects on grassland nitrogen (N) cycling. They can accelerate or slow down soil net N mineralization depending on ecosystem productivity and grazing intensity. Yet, most studies only consider either ungulates or invertebrate herbivores, but not the combined effect of several functionally different vertebrate and invertebrate herbivore species or guilds. We assessed how a diverse herbivore community affects net N mineralization in subalpine grasslands. By using size‐selective fences, we progressively excluded large, medium, and small mammals, as well as invertebrates from two vegetation types, and assessed how the exclosure types (ET) affected net N mineralization. The two vegetation types differed in long‐term management (centuries), forage quality, and grazing history and intensity. To gain a more mechanistic understanding of how herbivores affect net N mineralization, we linked mineralization to soil abiotic (temperature; moisture; NO 3 − , NH 4 + , and total inorganic N concentrations/pools; C, N, P concentrations; pH; bulk density), soil biotic (microbial biomass; abundance of collembolans, mites, and nematodes) and plant (shoot and root biomass; consumption; plant C, N, and fiber content; plant N pool) properties. Net N mineralization differed between ET, but not between vegetation types. Thus, short‐term changes in herbivore community composition and, therefore, in grazing intensity had a stronger effect on net N mineralization than long‐term management and grazing history. We found highest N mineralization values when only invertebrates were present, suggesting that mammals had a negative effect on net N mineralization. Of the variables included in our analyses, only mite abundance and aboveground plant biomass explained variation in net N mineralization among ET. Abundances of both mites and leaf‐sucking invertebrates were positively correlated with aboveground plant biomass, and biomass increased with progressive exclusion. The negative impact of mammals on net N mineralization may be related partially to (1) differences in the amount of plant material (litter) returned to the belowground subsystem, which induced a positive bottom‐up effect on mite abundance, and (2) alterations in the amount and/or distribution of dung, urine, and food waste. Thus, our results clearly show that short‐term alterations of the aboveground herbivore community can strongly impact nutrient cycling within ecosystems independent of long‐term management and grazing history.

Efficient and graded gene expression in glia and neurons of primary cerebellar cultures transduced by lentiviral vectors - Sujeet Kumar; Katrin Zimmermann; Hiroyuki Hioki; Alexander Pfeifer; Stephan L. Baader (Histochemistry and Cell Biology, 2015)

Flux-based ozone risk assessment for adult beech forests - Ludger Grünhage; Rainer Matyssek; Karl-Heinz Häberle; Gerhard Wieser; Ursula Metzger; Michael Leuchner; Annette Menzel; Jochen Dieler; Hans Pretzsch; Winfried Grimmeisen; Lothar Zimmermann; Stephan Raspe (Trees, 2012)

Increasing soil methane sink along a 120‐year afforestation chronosequence is driven by soil moisture - David Hiltbrunner; Stephan Zimmermann; Saeed Karbin; Frank Hagedorn; Pascal A. Niklaus (Global Change Biology, 2012)
Upland soils are important sinks for atmospheric methane ( CH 4 ), a process essentially driven by methanotrophic bacteria. Soil CH 4 uptake often depends on land use, with afforestation generally increasing the soil CH 4 sink. However, the mechanisms driving these changes are not well understood to date. We measured soil CH 4 and N 2 O fluxes along an afforestation chronosequence with Norway spruce (Picea abies L.) established on an extensively grazed subalpine pasture. Our experimental design included forest stands with ages ranging from 25 to >120 years and included a factorial cattle urine addition treatment to test for the sensitivity of soil CH 4 uptake to N application. Mean CH 4 uptake significantly increased with stand age on all sampling dates. In contrast, CH 4 oxidation by sieved soils incubated in the laboratory did not show a similar age dependency. Soil CH 4 uptake was unrelated to soil N status (but cattle urine additions stimulated N 2 O emission). Our data indicated that soil CH 4 uptake in older forest stands was driven by reduced soil water content, which resulted in a facilitated diffusion of atmospheric CH 4 into soils. The lower soil moisture likely resulted from increased interception and/or evapotranspiration in the older forest stands. This mechanism contrasts alternative explanations focusing on nitrogen dynamics or the composition of methanotrophic communities, although these factors also might be at play. Our findings further imply that the current dramatic increase in forested area increases CH 4 uptake in alpine regions.

Agroforestry species of the Bolivian Andes: an integrated assessment of ecological, economic and socio-cultural plant values - Regine Brandt; Heike Zimmermann; Isabell Hensen; Juan Carlos Mariscal Castro; Stephan Rist (Agroforestry Systems, 2012)

Effects of Land-Use Change on Carbon Stocks in Switzerland - Janine Bolliger; Frank Hagedorn; Jens Leifeld; Jürgen Böhl; Stephan Zimmermann; Reto Soliva; Felix Kienast (Ecosystems, 2008)

Extension for private forest owners: Insights from a representative opinion poll in Switzerland - Stephan Wild-Eck; Willi Zimmermann; Franz Schmithüsen (Small-scale Forestry, 2006)

Specific detection and semi-quantitative analysis of TRPC4 protein expression by antibodies - Veit Flockerzi; Christine Jung; Thomas Aberle; Marcel Meissner; Marc Freichel; Stephan E. Philipp; Wolfgang Nastainczyk; Patrick Maurer; Richard Zimmermann (Pflügers Archiv - European Journal of Physiology, 2005)

Laboratory and field evaluation of different formulations of Metarhizium anisopliae var. acridum submerged spores and aerial conidia for the control of locusts and grasshoppers - A. Kassa; D. Stephan; S. Vidal; G. Zimmermann (BioControl, 2004)